Harmonizing evidence-based practice, implementation context, and implementation strategies with user-centered design: a case example in young adult cancer care - Emily R. Haines; Alex Dopp; Aaron R. Lyon; Holly O. Witteman; Miriam Bender; Gratianne Vaisson; Danielle Hitch; Sarah Birken (Implementation Science Communications, 2021)
Abstract Background Attempting to implement evidence-based practices in contexts for which they are not well suited may compromise their fidelity and effectiveness or burden users (e.g., patients, providers, healthcare organizations) with elaborate strategies intended to force implementation. To improve the fit between evidence-based practices and contexts, implementation science experts have called for methods for adapting evidence-based practices and contexts and tailoring implementation strategies; yet, methods for considering the dynamic interplay among evidence-based practices, contexts, and implementation strategies remain lacking. We argue that harmonizing the three can be facilitated by user-centered design, an iterative and highly stakeholder-engaged set of principles and methods. Methods This paper presents a case example in which we used a three-phase user-centered design process to design and plan to implement a care coordination intervention for young adults with cancer. Specifically, we used usability testing to redesign and augment an existing patient-reported outcome measure that served as the basis for our intervention to optimize its usability and usefulness, ethnographic contextual inquiry to prepare the context (i.e., a comprehensive cancer center) to promote receptivity to implementation, and iterative prototyping workshops with a multidisciplinary design team to design the care coordination intervention and anticipate implementation strategies needed to enhance contextual fit. Results Our user-centered design process resulted in the Young Adult Needs Assessment and Service Bridge (NA-SB), including a patient-reported outcome measure and a collection of referral pathways that are triggered by the needs young adults report, as well as implementation guidance. By ensuring NA-SB directly responded to features of users and context, we designed NA-SB for implementation, potentially minimizing the strategies needed to address misalignment that may have otherwise existed. Furthermore, we designed NA-SB for scale-up; by engaging users from other cancer programs across the country to identify points of contextual variation which would require flexibility in delivery, we created a tool intended to accommodate diverse contexts. Conclusions User-centered design can help maximize usability and usefulness when designing evidence-based practices, preparing contexts, and informing implementation strategies—in effect, harmonizing evidence-based practices, contexts, and implementation strategies to promote implementation and effectiveness.